2011
DOI: 10.1111/j.1365-2311.2011.01299.x
|View full text |Cite
|
Sign up to set email alerts
|

Fitness costs and benefits of shelter building and leaf trenching behaviour in a pyralid caterpillar

Abstract: 1. Shelter building and petiole trenching in the Lepidoptera is a behaviour that mediates ecological pressures including those exerted by both food plants and natural enemies.2. Fitness costs and benefits of trenching and shelter-building behaviour related to predation and larval performance were investigated in a pyralid species that inhabits and feeds on leaf shelters.3. Assays comparing the performance of caterpillars feeding on trenched versus nontrenched foliage and fresh versus dry leaves were conducted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Trenching is likely to facilitate the rest of the shelter-building process because it provokes a turgidity loss that facilitates leaf folding (Ide 2004;Hansell 2005). It may also have a nutritional function, since Lepidomys caterpillars feeding inside their shelters have been observed to have higher pupal mass than caterpillars feeding on non-trenched tissue (Abarca and Boege 2011). Trenching usually prevents induction and flux of resin and latex (Dussourd and Denno 1991;Chambers et al 2007), which could be its function in this system.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Trenching is likely to facilitate the rest of the shelter-building process because it provokes a turgidity loss that facilitates leaf folding (Ide 2004;Hansell 2005). It may also have a nutritional function, since Lepidomys caterpillars feeding inside their shelters have been observed to have higher pupal mass than caterpillars feeding on non-trenched tissue (Abarca and Boege 2011). Trenching usually prevents induction and flux of resin and latex (Dussourd and Denno 1991;Chambers et al 2007), which could be its function in this system.…”
Section: Discussionmentioning
confidence: 98%
“…Benefits include light shielding (Sandberg and Berenbaum 1989), microclimate enhancement (Hunter and Willmer 1989;Larsson et al 1997), protection from predators (Damman 1987;Eubanks et al 1997), and increase in plant quality (Sandberg and Berenbaum 1989;Sagers 1992). In the present study, the shelters that were found provided defense against predators and, to a lesser extent, nutritional benefits, which change with shelter occupation time (Abarca and Boege 2011). Potential costs of the shelter-building habit include the time and energy spent building them (Fitzgerald et al 1991;Berenbaum et al 1993;Fitzgerald and Clark 1994) as well as increased risk of parasitoid attack relative to non-shelterbuilding species .…”
Section: Introductionmentioning
confidence: 98%
“…Almost all animal species face predation, thus are required to avoid predators or defend themselves to survive and reproduce (Rosier & Langkilde, 2011;Vail & McCormick, 2011). Many defenseless species use simple and common strategies such as evading predators, inhabiting concealed areas, or seeking refuges (Sih et al, 1992;Francke et al, 2008;Abarca & Boege, 2011), some others are equipped with chemical compounds which make them unprofitable for or toxic to potential predators (Santos et al, 2003). The evolution of such chemical defense is usually accompanied by the acquisition of a variety of signals (Tullberg et al, 2000;Gohli & Hogstedt, 2009;Johansen et al, 2011) that warn the predators to avoid attacking the unprofitable prey, a widespread phenomenon known as aposematism (Eisner & Grant, 1981;Rudh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Tseng et al, 2011) and/or more rarely serve as signals (reviewed in Schaedelin and Taborsky, 2009). Several studies have already evaluated the cost of secretion of the material from which the structures are made (Eisner, 1994;Stevens et al, 1999;McKie, 2004;Hansell, 2005;Mondy et al, 2011) and the energetic costs, which include metabolic energy expended gathering materials and building the structure (Abarca and Boege, 2011;Mondy et al, 2011). However, the non-energetic costs of construction behaviour remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%